Exploring take-back recovery strategies in the Circular Economy: A Multiple Case Study Analysis - Choi, Yoon Jung; Dong, Jiayuan; Pyon, Jaehoon (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
The take-back of end-of-use products has gained increasing importance with the growing focus on the circular economy. However, not all take-back strategies have been thoroughly explored and understood in relation to consumer engagement. This study examines the role of take-back recovery approaches and strategies in the circular economy, integrating a product design and service lens to address consumer return practices. The research identifies four distinct opportunities under the take-back umbrella: Direct Reuse, Ease of Disassembly, Final Recovery, and Safe Disposal. For each opportunity, potential sub-opportunities are identified and expanded upon. Through a multiple case study analysis, these sub-opportunities are further developed using a "Design for X" approach to form nine distinct take-back strategies. This research emphasizes that the appropriateness of a take-back strategy depends on various factors, such as consumer behavior and context, industry specifics, and material flows. The study highlights the critical role of take-back systems and returns behavior in promoting circular product development and consumption.